Unlocking the Potential of Carica papaya L.: A Comprehensive Review on Its Antiviral Activity and Therapeutic Role in Dengue Management - Dluya Samuel Thagriki (African Journal of Biochemistry and Molecular Biology Research, 2026)
Dengue is a rapidly expanding global health problem for which no specific antiviral therapy is currently available, leaving disease management largely supportive and symptomatic. Severe thrombocytopenia is a major clinical concern in dengue infection, while prophylactic platelet transfusion can be costly and may not always be readily accessible. Carica papaya leaf juice (CPLJ) has been used off-label in the management of dengue fever and dengue haemorrhagic fever and has been reported to increase platelet counts in thrombocytopenic children and adults with minimal adverse effects. This review synthesizes evidence on the antiviral activity and therapeutic potential of CPLJ and C. papaya leaf extracts in the treatment and recovery of dengue-infected patients. It examines recent findings from in vitro and in vivo studies, documented clinical trials, traditional applications, and research on the phytochemicals, amino acids, and other bioactive constituents of C. papaya leaves. The reviewed evidence indicates that CPLJ and its extracts may inhibit dengue virus activity, increase platelet counts, and support recovery among patients with dengue fever and dengue haemorrhagic fever. These findings suggest that C. papaya leaves represent a promising natural source of bioactive compounds for developing supportive or antiviral interventions against dengue virus infection. Nevertheless, further rigorous pharmacological and clinical investigations are required to establish standardized formulations, therapeutic dosages, mechanisms of action, safety profiles, and clinical efficacy.